The optimisation of throwing movements with evolutionary algorithms on the basis of multibody systems - Bächle, F. (International Journal of Computer Science in Sport, 2002)
The objective of the research is to find a pattern of movements of kinetic links that will result in a maximum throwing distance. The solution of the problem shall be approached with different methods: On the one hand by the formulation of the movements on the basis of classical physics, on the other hand by computer simulation with the help of evolutionary algorithms and algorithms based on models. In the following the arrangement, first experiences and first conclusions with the use of the evolutionary algorithm (in fact the evolution strategy) will be described.